2005
DOI: 10.1103/physrevlett.94.083001
|View full text |Cite
|
Sign up to set email alerts
|

ac Electric Trap for Ground-State Molecules

Abstract: We here report on the realization of an electrodynamic trap, capable of trapping neutral atoms and molecules in both low-field and high-field seeking states. Confinement in three dimensions is achieved by switching between two electric field configurations that have a saddle point at the center of the trap, i.e., by alternating a focusing and a defocusing force in each direction. The ac trapping of 15ND(3) molecules is experimentally demonstrated, and the stability of the trap is studied as a function of the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
128
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(136 citation statements)
references
References 22 publications
2
128
0
6
Order By: Relevance
“…A recent theoretical study has shown that sympathetic cooling of CaD( 2 ) and OH( 2 ) molecules in low-field-seeking Zeeman states may be facilitated by superimposed electric and magnetic fields [21]. We note that certain trapping techniques employing ac electric [22], optical dipole [23], or microwave [24] fields, allow for trapping ground-state molecules, thereby eliminating the possibility of collisional relaxation. At their present stage of development, however, these techniques are less advanced than magnetic or electrostatic trapping [1].…”
Section: Introductionmentioning
confidence: 99%
“…A recent theoretical study has shown that sympathetic cooling of CaD( 2 ) and OH( 2 ) molecules in low-field-seeking Zeeman states may be facilitated by superimposed electric and magnetic fields [21]. We note that certain trapping techniques employing ac electric [22], optical dipole [23], or microwave [24] fields, allow for trapping ground-state molecules, thereby eliminating the possibility of collisional relaxation. At their present stage of development, however, these techniques are less advanced than magnetic or electrostatic trapping [1].…”
Section: Introductionmentioning
confidence: 99%
“…3D trapping by 3 phase electric dipole fields [20] or by an oscillating hexapole field superimposed on a static homogeneous field [21] has been proposed. The latter scheme has recently been demonstrated in trapping cold polar molecules [22].…”
mentioning
confidence: 99%
“…3D trapping by 3 phase electric dipole fields [20] or by an oscillating hexapole field superimposed on a static homogeneous field [21] has been proposed. The latter scheme has recently been demonstrated in trapping cold polar molecules [22].Here we consider 3D electrodynamic trapping with two-phase electric-dipole field, which will allow planar geometry that is suitable to be used with atom chips [23]. In order to illustrate the scheme, we first assume two spherical electrodes with radius b placed at ±d either on the x (or y) axis, kept at voltages ±V 0 as shown in …”
mentioning
confidence: 99%
“…The first demonstration of ac electric trapping was car- * Electronic address: schlunk@fhi-berlin.mpg.de ried out for ammonia molecules using a cylindrically symmetric trap with a depth of several millikelvins [11]. Similar trap depths were later obtained for the same molecule with a linear ac trap [12].…”
Section: Introductionmentioning
confidence: 75%